Search for High-energy Neutrinos from Ultraluminous Infrared Galaxies with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Humboldt-Universität zu Berlin, 2022)
Ultraluminous infrared galaxies (ULIRGs) have infrared luminosities LIR ≥ 1012L⊙, making them the most luminous objects in the infrared sky. These dusty objects are generally powered by starbursts with star formation rates that exceed 100 M⊙ yr−1, possibly combined with a contribution from an active galactic nucleus. Such environments make ULIRGs plausible sources of astrophysical high-energy neutrinos, which can be observed by the IceCube Neutrino Observatory at the South Pole. We present a stacking search for high-energy neutrinos from a representative sample of 75 ULIRGs with redshift z ≤ 0.13 using 7.5 yr of IceCube data. The results are consistent with a background-only observation, yielding upper limits on the neutrino flux from these 75 ULIRGs. For an unbroken E−2.5 power-law spectrum, we report an upper limit on the stacked flux ${{\rm{Φ }}}_{{ν }_{μ }+{\bar{ν }}_{μ }}^{90 % }=3.24× {10}^{-14}\,TeV^{-1}\,{cm}^{-2}\,{{\rm{s}}}^{-1}\,{(E/10\,TeV)}^{-2.5}$ at 90% confidence level. In addition, we constrain the contribution of the ULIRG source population to the observed diffuse astrophysical neutrino flux as well as model predictions. Peer Reviewed